2013
DOI: 10.3109/08958378.2013.806613
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of waterpipe smoking on lung function and exercise capacity in a pilot study of healthy participants

Abstract: Acute WTS appears to induce impairment in lung function and exercise capacity. Larger studies are warranted to further characterize the nature and extent of such impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 37 publications
0
66
0
6
Order By: Relevance
“…10,25,32,33 To the best of our knowledge, studies on maximal and submaximal aerobic capacities of ENS are rare: 10,25,33 two studies had evaluated the chronic effects of narghile smoke on passive animal smokers 33 and on human ENS, 10 and one evaluated its acute effects on human ENS. 25 Sulaiman 33 studied an experimental model of pregnant rats exposed to narghile smoke (daily for 10 min from days 2 to 18 of pregnancy) and examined the effect of smoking on locomotor activity of juvenile rats (ambulatory and stereotype behavior of offspring measured at the age of 30 d). He found that the total ambulatory activity and stereotype movements of exposed rats were 21% (P ϭ .08) and 26% (P ϭ .03) lower than those of matched controls, respectively, and that the decreased rates of ambulatory activity and stereotype movements in exposed rats were 28% (P ϭ .09) and 10-fold (P Ͻ .05) lower than those in non-exposed rats, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…10,25,32,33 To the best of our knowledge, studies on maximal and submaximal aerobic capacities of ENS are rare: 10,25,33 two studies had evaluated the chronic effects of narghile smoke on passive animal smokers 33 and on human ENS, 10 and one evaluated its acute effects on human ENS. 25 Sulaiman 33 studied an experimental model of pregnant rats exposed to narghile smoke (daily for 10 min from days 2 to 18 of pregnancy) and examined the effect of smoking on locomotor activity of juvenile rats (ambulatory and stereotype behavior of offspring measured at the age of 30 d). He found that the total ambulatory activity and stereotype movements of exposed rats were 21% (P ϭ .08) and 26% (P ϭ .03) lower than those of matched controls, respectively, and that the decreased rates of ambulatory activity and stereotype movements in exposed rats were 28% (P ϭ .09) and 10-fold (P Ͻ .05) lower than those in non-exposed rats, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…10,25,32,33 Characterizing such changes can add to a more comprehensive understanding of narghile smoking impact on critical physiological measures, and generated information can serve as a deterrent when counseling smokers against this seemingly harmless habit. 10,25,32,33 To the best of our knowledge, studies on maximal and submaximal aerobic capacities of ENS are rare: 10,25,33 two studies had evaluated the chronic effects of narghile smoke on passive animal smokers 33 and on human ENS, 10 and one evaluated its acute effects on human ENS. 25 Sulaiman 33 studied an experimental model of pregnant rats exposed to narghile smoke (daily for 10 min from days 2 to 18 of pregnancy) and examined the effect of smoking on locomotor activity of juvenile rats (ambulatory and stereotype behavior of offspring measured at the age of 30 d).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations